Demographic responses of grassland songbirds to rangeland management in the tallgrass prairie - Verheijen, Bram Hendrik Ferdinand (Kansas State University, 2017)
Grasslands are among the most rapidly declining ecosystems in the world. The Flint Hills ecoregion contains one of the largest remaining tracts of tallgrass prairie, but most of the area is managed with high densities of grazing animals and frequent prescribed burns, thereby reducing variation in vegetative structure. A homogeneous landscape leads to lower diversity and abundance of wildlife species, including grassland songbirds. Patch-burn grazing management has been proposed to more closely match the historical interaction between fire and selective grazing by native ungulates. Pastures managed with patch-burn grazing have a greater variety of vegetative structure and plant species composition, and as a result, higher species diversity, abundance, and reproductive success of grassland birds. However, past work has not considered potential effects of regional variation in predation risk and rates of brood parasitism by Brown-headed Cowbirds (Molothrus ater), or annual variation in climatic conditions on the effects of patch-burn grazing management on the reproductive success of grassland songbirds. Over a six year period and at two tallgrass prairie sites, I tested the effects of patch-burn grazing on the reproductive success of three native grassland songbird species, Dickcissels (Spiza americana), Eastern Meadowlarks (Sturnella magna), and Grasshopper Sparrows (Ammodramus savannarum), as well as subsequent effects on the space use, movements, and survival of fledgling Dickcissels. I found only minor effects of patch-burn grazing on the reproductive success of grassland songbirds, supporting previous studies that show that patch-burn grazing does not have negative effects on demographic rates of grassland songbirds. Management regime did not affect densities or territory size of male Dickcissels, but bird densities tended to be higher and territories tended to be smaller on patches within the patch-burn grazing treatment that were burned in the previous year. Thus, patch-burn grazing management might benefit Dickcissel populations by providing higher quality breeding habitat in unburned patches. Last, I found evidence for a potential tradeoff between habitat selection for nests vs. fledglings of Dickcissels in some rangeland management strategies. Parents that realized high reproductive success by nesting in pastures with lower cowbird densities, produced fledglings that faced high rates of depredation by snakes and showed greater movements away from those pastures. Survival rates and movements of Dickcissel fledglings were low, especially during the first week after leaving the nest, which stresses the importance of local habitat conditions. At a larger spatial scale, I tested whether regional differences in habitat structure could drive variation in apparent survival of grassland songbirds. I found that grassland- and shrubland-breeding species had higher estimates of apparent survival than forest-breeding species, contrary to the prevailing viewpoint that birds breeding in dynamic landscapes, such as frequently burned grasslands, should show lower apparent survival than species that breed in woody habitats. The results of my field study show that restoring the historical interaction between fire and grazing on the landscape via patch-burn grazing management could benefit grassland songbirds. Moreover, my dissertation is the first study that tests the effects of patch-burn grazing management on the survival and movements of fledgling Dickcissels, and shows that high cowbird densities can cause a tradeoff between different life-stages. Future conservation efforts should take into account regional variation in species abundance, predator community composition and abundance of Brown-headed Cowbirds when assessing the effects of rangeland management on the demography of grassland songbirds.
Keywords: Grassland; Songbird; Demography; Population; Ecology; Survival